The relationship between diabetes mellitus (DM) risk factors and random blood sugar levels (RBSL) in managerial and non-managerial positions in the local government of Bener Meriah Regency - Hajjah Hajjah; Fahmi Ichwansyah; Meutia Zahara; Basri Aramico; Asnawi Abdullah (Science Midwifery, 2026)
Fasting Blood Sugar Level (FBSL) as one of the efforts to detect DM. The study aims to determine the risk factors of DM on FBSL in managerial and non-managerial positions (civil servants) in Bener Meriah Regency. The study used a cross-sectional design. The research sample consisted of 81 managerial and 102 non-managerial respondents. Purposive sampling was used. The study period was from February 20 to June 7, 2024. Data collection involved measurements (height, weight to calculate BMI), blood pressure checks, and KGDS. A questionnaire (IPAQ) was used for interviews on physical activity, and a questionnaire (Riskesdas) from 2018 was used for interviews on risk factors for low fiber consumption and high sugar, salt, and fat consumption. Analysis of Mann Whitney Test and Multiple Logistic Regression data. The results showed that there was a relationship between KGDS and BMI (OR= 2.48; 95%CI=2.48; p-value=0.007). There was no relationship between KGDS and blood pressure (OR= 1.66; 95%CI=0.82-3.35; p-value=0.1520). There is no relationship between KGDS and physical inactivity (OR=1.80; 95% CI=0.82-3.93 p-value=0.1307). There is no relationship between KGDS and low fiber consumption (OR=1.15; 95% CI=0.50-2.61 p-value=0.74). There was no association between KGDS and high sugar, salt, and fat intake (OR=0.90; 95% CI=0.41-1.94; p-value=0.7828). There was no association between group and KGDS occurrence (OR=1.39; 95% CI=0.76-2.53 p-value=0.272). There was no association between random blood glucose levels (KGDS) and blood pressure, physical activity, and dietary patterns. Regular KGDS testing and the implementation of physical activity and balanced nutrition are still recommended.